Cost-Nutrition Assessment Guideline of School Feeding Program - Phuong Vichea, Vanna; Sockcheng, Sim; Sombath, KEO (WorldFish, 2024)
The “Cost-Nutrition Assessment Guideline for School Feeding Program in Cambodia” utilizes a modified SEEM (Scope, Economic Components, Evaluation, and Measurement) framework to evaluate the cost-effectiveness, sustainability, and nutritional impact of decentralized school feeding programs. The framework assesses program boundaries, resource allocation, infrastructure, cost-effectiveness, and nutritional sufficiency. Key metrics include recurring costs (e.g., food, labor) and non-recurring costs (e.g., equipment, infrastructure), with a focus on cost per beneficiary and macro/micronutrient content of meals. Integrating school gardening into the program enhances cost-effectiveness by reducing food procurement costs and improving meal quality. Findings reveal that low-calorie breakfasts negatively impact children’s energy, focus, and academic performance, increasing the risk of nutritional deficiencies. The guideline emphasizes tailored strategies to improve breakfast nutritional content, ensure cost-efficiency, and foster program sustainability. The SEEM framework serves as a vital tool, empowering policymakers to optimize resource allocation and achieve better health and educational outcomes for Cambodian students.